New developments in the combination treatment of COPD: focus on umeclidinium/vilanterol - Cazzola M; Segreti A; Matera MG (Dove Medical Press, 2013)
Mario Cazzola,1 Andrea Segreti,1 Maria Gabriella Matera2 1Department of System Medicine, University of Rome 'Tor Vergata', Rome, Italy; 2Department of Experimental Medicine, Second University, Naples, Italy Abstract: An increasing body of evidence suggests that the long-acting muscarinic antagonist (LAMA)/long-acting β2-agonist (LABA) combination appears to play an important role in maximizing bronchodilation, with studies to date indicating that combining different classes of bronchodilators may result in significantly greater improvements in lung function compared to the use of a single drug, and that these combinations are well tolerated in patients with moderate-to-severe chronic obstructive pulmonary disease (COPD). An inhaled, fixed-dose combination of two 24-hour bronchodilators, the LAMA umeclidinium and the LABA vilanterol, is under development as a once-daily treatment for COPD. The efficacy of both mono-components has already been demonstrated. The information currently available suggests that umeclidinium/vilanterol is an effective once-daily dual bronchodilator fixed-dose combination in the treatment of COPD. However, it remains to be seen if it compares favorably with current therapies. Moreover, the question remains whether umeclidinium/vilanterol fixed-dose combination, which significantly improves FEV1, is also associated with improvements in other outcome measures that are important to COPD patients. Keywords: muscarinic antagonist, dual bronchodilation, COPD